SPEAKS study: study protocol of a multisite feasibility trial of the Specialist Psychotherapy with Emotion for Anorexia in Kent and Sussex (SPEAKS) intervention for outpatients with anorexia nervosa or otherwise specified feeding and eating disorders, anorexia nervosa type. Issue 2 (22nd February 2022) - Oldershaw, Anna; Lavender, Tony; Basra, Randeep; Startup, Helen
Abstract : Introduction: Anorexia nervosa (AN) is a severe mental health condition associated with high mortality rates and significantly impaired quality of life. National guidelines outline psychotherapeutic interventions as treatments of choice for adults with AN, but outcomes are limited and therapy drop-out high, resulting in calls for new innovative treatments. The Specialist Psychotherapy with Emotion for Anorexia in Kent and Sussex (SPEAKS) research programme sought to develop the SPEAKS intervention avoiding some difficulties inherent in development of earlier interventions, such unclear hypotheses about change processes. SPEAKS focuses on a core hypothesised maintaining factor (emotional experience) with clear proposed model of change. The current feasibility trial aims to provide an initial test of SPEAKS and inform design of a full randomised controlled trial protocol. Methods and analysis: This study employs a multisite, single-arm, within-group, mixed-methods design. Up to 60 participants (36 therapy completers) meeting inclusion criteria will be offered the SPEAKS intervention instead of treatment-as-usual (TAU). SPEAKS is a weekly psychotherapy lasting nine to 12 months, provided by trained and experienced eating disorders therapists. All other clinical input remains inline with TAU. Acceptability will be assessed using VAS scales and end of therapy interview. Reach and recruitment, such as recruitment yield, will be monitored. To support sample size estimation and economic estimation, data pertaining to eating disorder-related symptoms will be recorded every 3 months, alongside service usage and intervention-specific measures. Videoed therapy sessions will inform model adherence. Additional analyses coding videoed therapy will test SPEAKS change process hypotheses. Ethics and dissemination: Ethical approval has been granted by London–Bromley Research Ethics Committee (NHS Rec Reference: 19/LO/1530). Data will be disseminated via high-impact, peer-reviewed journals (Open Access preferred), conferences, service user and charity networks (eg, UK charity BEAT) and through a free open conference hosted by National Health Service Trusts and Higher Education Institutions. Trial registration number: ISRCTN11778891 . Trial status: Recruitment began on 12 December 2019 and ends on 28 February 2021. All data will be collected and the trial ended by 28 February 2022. Protocol version: SPEAKS protocol V.3.0 (30 August 2020). Changes were made to the original protocol due to the COVID-19 pandemic. A further set of changes were made to incorporate the measures of change processes, resulting in this being the third version of the protocol.